2020
DOI: 10.1016/j.joca.2020.02.630
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and progression of ankle osteoarthritis: the Johnston county osteoarthritis project

Abstract: significant difference (P<0.05) between the effective rate of the experimental group and that of the control group. All indicators of KOOS were improved, with the significant differences in symptom score, sports score and entertainment ability score, and the life quality reladsvblmadmted to the knee (P < 0.05). The levels of serumIL-1b,TNFa were all decreased in the experimental group, with a significant difference in the degree of IL-1b decrease (P<0.05). Conclusions: Qufengzhitong Capsule is effective in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The higher prevalence of radiographic ankle OA in men is consistent with one other study [8], but is contrary to another study that reports more symptomatic ankle OA in women [1]. As the prevalence of ankle and/or foot pain is higher in women, this might explain the contradicting association between sex and symptomatic compared to radiographic ankle OA [25].…”
Section: Radiographic Ankle Oa In Subgroups Of Patientssupporting
confidence: 81%
See 2 more Smart Citations
“…The higher prevalence of radiographic ankle OA in men is consistent with one other study [8], but is contrary to another study that reports more symptomatic ankle OA in women [1]. As the prevalence of ankle and/or foot pain is higher in women, this might explain the contradicting association between sex and symptomatic compared to radiographic ankle OA [25].…”
Section: Radiographic Ankle Oa In Subgroups Of Patientssupporting
confidence: 81%
“…We did not adjust for determinants reported in other studies such as occupation, smoking status, ethnicity, concomitant foot or knee joint OA, knee joint hypermobility and foot structure [1,5,6,8,22,24], as they were not available. Due to the cross-sectional study design, no causal inferences can be drawn from the reported associations.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation